Freeform Shadow Boundary Editing. (6th May 2013) - Mattausch, O.; Igarashi, T.; Wimmer, M.
Abstract: We present an algorithm for artistically modifying physically based shadows. With our tool, an artist can directly edit the shadow boundaries in the scene in an intuitive fashion similar to freeform curve editing. Our algorithm then makes these shadow edits consistent with respect to varying light directions and scene configurations, by creating a shadow mesh from the new silhouettes. The shadow mesh helps a modified shadow volume algorithm cast shadows that conform to the artistic shadow boundary edits, while providing plausible interaction with dynamic environments, including animation of both characters and light sources. Our algorithm provides significantly more fine‐grained local and direct control than previous artistic light editing methods, which makes it simple to adjust the shadows in a scene to reach a particular effect, or to create interesting shadow shapes and shadow animations. All cases are handled with a single intuitive interface, be it soft shadows, or (self‐)shadows on arbitrary receivers.